Swimming against the populist tide: lessons from Central and Eastern Europe - Perevezentseva, Anastassiya (Frontiers in Political Science, 2025)
Right-wing populism poses a persistent threat to democratic governance in Central and Eastern Europe, sparking widespread anti-populist mobilization across the region. This study examines why some anti-populist social movements in the Visegrád Four succeed electorally while others do not, using process tracing to analyze variation across comparable political and historical contexts. It identifies three recurring features among the successful cases: sustained mobilization, inclusive framing, and operation within contexts marked by coherent democratic elites. The findings contribute to debates on democratic backsliding and offer valuable insights for scholars, activists, and policymakers seeking to counter right-wing populists holding electoral power.